The Educational Inspection. An Institutional Qualification Model in the Face of the Challenges of the 21th Century. Structural And Functional Vision - Campos Barrionuevo, Blas (Avances en Supervisión Educativa, 2024)
Through this work we have attempted to analyze certain elements, both structural and functional, referring to Educational Inspection/Supervision in the Spanish educational (school) system. To do this, starting from a theoretical-doctrinal and legal analysis of educational quality, as a guiding principle of our educational system within the framework of Organic Law 2/2006, of May 3, on Education –LOE–, given its new wording after the promulgation of Organic Law 3/2020, of December 29, which modifies the LOE –LOMLOE– (LOE-TC hereinafter), we have proceeded to define and describe a certain model of institutional quality, that it was the starting point for said study, in order to propose two models for updating and qualifying the supervisory function per se; namely: a) a (new) structural model for access to said Teaching Body, and b) a (new) (functional) model for the best development and performance of the functions inherent to supervisory work at a global level, calling to this last «eco-inspection model». Although there are numerous models and paradigms in the field of action and knowledge of Educational Supervision/Inspection today, especially in its functional sphere, we want to enrich this list of models, generating at the same time a broad overall reflection for the permanent improvement of the supervisory function in general.Finally, and in a more structural dimension, we have analyzed the access models to the Corps of Inspectors in Spain, approximately over the last twenty-five years, in an attempt to make a well-founded contrast, providing a possible improvement in them, in a continuous process of improvement and refinement of said Technical Service – Education Inspection.